2004
DOI: 10.1091/mbc.e04-04-0342
|View full text |Cite
|
Sign up to set email alerts
|

Rab22a Regulates the Recycling of Membrane Proteins Internalized Independently of Clathrin

Abstract: Plasma membrane proteins that are internalized independently of clathrin, such as major histocompatibility complex class I (MHCI), are internalized in vesicles that fuse with the early endosomes containing clathrin-derived cargo. From there, MHCI is either transported to the late endosome for degradation or is recycled back to the plasma membrane via tubular structures that lack clathrin-dependent recycling cargo, e.g., transferrin. Here, we show that the small GTPase Rab22a is associated with these tubular re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
253
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(278 citation statements)
references
References 47 publications
(73 reference statements)
23
253
0
Order By: Relevance
“…The accumulation of endocytic tracers in these enlarged endosomes indicates that the internalization step of endocytosis is not significantly impaired in rab-10 mutants, but rather the recycling of the fluid back to the body cavity is defective. We also found that basolaterally localized transmembrane cargo proteins thought to be endocytosed by both clathrin-mediated and clathrin-independent mechanisms label the enlarged endosomes, consistent with the proposal that rab-10, like rme-1, regulates endocytic recycling but not endocytosis per se and that clathrin-dependent and clathrin-independent cargo are likely to meet in the endosomal system, as has been suggested in mammalian cell systems (Naslavsky et al, 2004;Weigert et al, 2004). Because all exogenous tracers that we have identified for studying endocytosis in C. elegans are sent to lysosomes when internalized apically but not recycled back to the intestinal lumen, we have not been able to determine if rab-10 or rme-1 mutations also affect apical recycling in the worm intestine.…”
Section: Rab-10 Is Required For Endocytic Recycling In the Worm Intessupporting
confidence: 89%
See 2 more Smart Citations
“…The accumulation of endocytic tracers in these enlarged endosomes indicates that the internalization step of endocytosis is not significantly impaired in rab-10 mutants, but rather the recycling of the fluid back to the body cavity is defective. We also found that basolaterally localized transmembrane cargo proteins thought to be endocytosed by both clathrin-mediated and clathrin-independent mechanisms label the enlarged endosomes, consistent with the proposal that rab-10, like rme-1, regulates endocytic recycling but not endocytosis per se and that clathrin-dependent and clathrin-independent cargo are likely to meet in the endosomal system, as has been suggested in mammalian cell systems (Naslavsky et al, 2004;Weigert et al, 2004). Because all exogenous tracers that we have identified for studying endocytosis in C. elegans are sent to lysosomes when internalized apically but not recycled back to the intestinal lumen, we have not been able to determine if rab-10 or rme-1 mutations also affect apical recycling in the worm intestine.…”
Section: Rab-10 Is Required For Endocytic Recycling In the Worm Intessupporting
confidence: 89%
“…In MDCK cells Rab4 has also been reported to associate with early endosomes and a later compartment named the common endosome, where is promotes apical delivery of transcytotic cargo (Mohrmann et al, 2002). Rab11 is primarily associated with recycling endosomes and has been reported to act after Rab4 in nonpolarized cells, mediating recycling endosome to PM transport of clathrin-dependent and clathrin-independent recycling cargo (Sheff et al, 1999;Weigert et al, 2004). In polarized cells Rab11 is primarily associated with the ARE and is thought to function in the transport of cargo from the ARE to the PM (Casanova et al, 1999;Sheff et al, 1999;Brown et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many CIE cargo proteins, such as the major histocompatibility complex class I (MHCI), the α-chain of the IL-2 receptor (TAC), CD59, CD44, and CD147, have been confirmed to follow the Arf6-associated CIE pathway, which is highly conserved from Caenorhabditis elegans to mammalian cells (3). Several players, including Rab10, Rab22, Rab35, Hook1, ALX-1, and RME-1/EHD-1, have been identified to modulate the recycling of CIE cargoes through different itineraries (3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Rab11a, a defining marker of ERC, interacts with many Rab11 family interaction proteins and regulates ERC traffic. 9 These three GTPases are therefore regarded as key regulatory components of trafficking to and from ERC, and presumably participate in crosspresentation. However, most of the work on the regulatory functions of these proteins was performed in cells deficient in crosspresentation; a definitive association thus remains speculative.…”
Section: Cellular and Molecular Immunologymentioning
confidence: 99%